The explorers [videorecording] a century of discovery - Kane, Dennis B.; Noxon, Nicolas; Skinner, Thomas; National Geographic Society, Washington, D.C.; WQED (Television station : Pittsburg, Pa.). ([Washington, D.C.] The Society, 1988)
An overview of a century's worth of geographical exploration marking the centennial of the National Geographic Society, with segments of Richard E. Byrd, Diane Fossey, Jane Goodall, Jacques Costeau and more.
VHS.
Narrated by E.G. Marshall; edited by Barry Nye; A.C.E.
Keywords: Bell, Alexander Graham; Grosvenor, Gilbert; National Geographic Society; Explorers; Archaeological expeditions; Scientific expeditions; Arctic regions -- Discovery and exploration; Polar regions -- Discovery and exploration